Study of the development priority in accordance with MARPOL at the Port of Semayang, Balikpapan, Indonesia - Putri, Destyariani Liana; Nurmawati; Wirawan, Muhammad Khaisar; Firsandi, Rahmat; Fernandito, Gerald (UIN Sunan Ampel Surabaya, 2026)
Effective port management requires prioritizing environmental compliance in accordance with international regulations such as MARPOL. This study aims to identify and rank the most critical MARPOL Annex V criteria affecting port environmental performance at Semayang Port, Balikpapan, using the Analytic Hierarchy Process (AHP). Expert respondents provided pairwise comparisons of four key criteria, and their relative importance was visualized using a bar chart. Results show that Ship Waste Disposal in the port area (0.3317) and Fuel Reporting (0.3243) are the top priorities, together accounting for over 65% of total importance. In contrast, Waste Reporting (0.1785) and Occupational Health and Safety Standards (0.1655) were lower-ranked, reflecting that operational pollution control and fuel management dominate decision-making priorities. These findings provide a structured framework for port authorities to allocate resources, phase MARPOL-related interventions, and enhance compliance. By focusing on the most impactful criteria, Semayang Port and other ports in Indonesia and Asia can advance toward sustainable, resilient, and environmentally responsible operations.